Topographic reconstruction and mechanical analysis of atomic layer deposited Al2O3/TiO2 nanolaminates by nanoindentation. (5th December 2016) - Coy, Emerson; Yate, Luis; Kabacińska, Zuzanna; Jancelewicz, Mariusz; Jurga, Stefan; Iatsunskyi, Igor
Abstract: A novel method of nanomechanical testing of multilayered Al2 O3 /TiO2 nanolaminates was implemented by the nanoindentation technique. The indentation data were reconstructed and filtered by a statistical analysis algorithm and presented as a function of the penetration depth of the indenter. Results show the increment of mechanical properties on the laminates as a function of the amorphous interfaces of the individual layers and the effective control of the wear rate of the structures for further applications. The results presented show both important insights on the mechanical behavior of nanolaminates and the further applicability of the reconstruction model for error reduction on mechanical testing of nanolaminate samples. Graphical Abstract: Highlights: Nanolaminate thin films of Al2 O3 /TiO2 with different bilayer density were prepared by ALD method. A new multidimensional reconstruction method was implemented to analyze the nanomechanical response of the samples. Mechanical response of the nanolaminates showed to be improved by layer thickness and follow the behavior of a nanocomposite coating. The method implemented allows the reconstruction of 4D mechanical data at the nanoscale.